2021
DOI: 10.3390/w13060798
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Macroinvertebrates Ecological Preferences and Trait-Based Indicators of Suspended Fine Sediment Effects in the Tsitsa River and Its Tributaries, Eastern Cape, South Africa

Abstract: The taxonomy-based response pattern of macroinvertebrates to sediment stress is well established, with tolerant taxa increasing in impacted conditions, while sensitive taxa decrease along a deteriorating water quality gradient. However, the distribution patterns of traits in response to environmental stress gradient, including suspended sediments, remain unclear, particularly in Africa, where trait-based studies are under-explored. We examined the distribution patterns of macroinvertebrate traits along a suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The transport of fine particles can result in a build-up on the organs, which disrupts the normal functioning of the organisms. Fine sediments also impair habitats by clogging the interstices and reducing oxygen levels in the hyporheic zone, decrease food availability by attenuating light needed for optimal algal growth and covering algal food for grazers, and reduce the quality and palatability as well as access to food for shredders [ 72 , 73 , 74 , 75 ]. Sedentary invertebrates and cemented eggs or clutches are also affected by fine sediment deposition by being buried, leading to a lack of access to food and a reduced oxygen supply [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transport of fine particles can result in a build-up on the organs, which disrupts the normal functioning of the organisms. Fine sediments also impair habitats by clogging the interstices and reducing oxygen levels in the hyporheic zone, decrease food availability by attenuating light needed for optimal algal growth and covering algal food for grazers, and reduce the quality and palatability as well as access to food for shredders [ 72 , 73 , 74 , 75 ]. Sedentary invertebrates and cemented eggs or clutches are also affected by fine sediment deposition by being buried, leading to a lack of access to food and a reduced oxygen supply [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many interrelated environmental factors, such as the water body size, the diversity of habitats or water chemistry affects the abundance of macroinvertebrates (in general and of individual groups), thus making it difficult to determine precisely which of them is the leading one. However, it can be assumed that a pivotal factor in the surveyed ponds was the specificity of the bottom substrate (Ntloko et al, 2021). The weathering of limestone rock led to the accumulation of a thick layer of unconsolidated clay sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have also found alterations and declines in aquatic invertebrate diversity, community composition and functional traits within regulated and anthropogenically influenced streams and riverine systems (Gallardo et al, 2008(Gallardo et al, , 2014Kuiper et al, 2014). However, there is a scarcity of research in Africa, despite being one of the most affected continents in terms of anthropogenic use of freshwater systems (Akamagwuna et al, 2022;Ntloko et al, 2021;Odume, 2020). de de Necker, Manfrin, et al, 2020;de Necker, Neswiswi, et al, 2020;Dube et al, 2015Dube et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…These organisms encompass a diverse group of species with a widespread distribution and range of traits and adaptations to ensure survival in various aquatic environments (de Necker et al., 2021 ; de Necker, Brendonck, et al., 2022 ; Dube et al., 2022 ; Jeffries et al., 2016 ; Lake, 2011 ; Wantzen et al., 2016 ). Furthermore, aquatic invertebrates are known to undergo shifts in community composition in response to anthropogenic stressors (Akamagwuna et al., 2022 ; Cai et al., 2017 ; Foster et al., 2015 ; Helson & Williams, 2013 ; Magbanua et al., 2010 ; Mangadze et al., 2019 ; Ntloko et al., 2021 ; Villastrigo & García‐Criado, 2017 ). As a result, aquatic invertebrate traits and sensitivities have successfully been used as a biomonitoring method to assess ecosystem health (Akamagwuna et al., 2022 ; de Necker et al., 2023 ; Magbanua et al., 2010 ; Mangadze et al., 2019 ; Ntloko et al., 2021 ; Odume, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation